First Language Influences on Non-Native Speakers’ Business Writing: A Cross-Cultural Study - Aimoldina, Aliya (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
Communication and socialization skills are a necessity in contemporary business community. If business professionals are not able to express their ideas clearly, concisely, and appropriately, it will be challenging for them to close international business deals and agrrements. In this context, bilateral trade and economic relations between Kazakhstan and other countries have been growing steadily over the past years. This paper focuses on the first language influences that may lead to communication breakdown and cross-cultural pragmatic failure as seen in the corpora of 200 business letters written in English by Kazakhstani business professionals to their international partners.